Krasnodar Krai - agro-industrial giant and tourist jewel of the Russian Federation - Bukvić Rajko M. (Zbornik Radova: Geografski institut "Jovan Cvijić", 2014)
This article provides a geographic and socio-economic description of Krasnodar Krai, one of the federal subjects of the complexly organized Russian Federation. Its size and population are comparable to the ones of smaller European countries, such as Austria, Czech Republic, Republic of Ireland or Denmark, Finland and Slovakia. In comparison to Serbia, this region is somewhat smaller and less densely populated. Its landscape and climate diversity, as well as an abundance of natural resources make a good starting point for a further economic and social development of the region. The agro-industrial complex and tourism are especially developed in this region and are considered its strong points both within Russia and outside its borders. The level of industrial cooperation between Serbia and Russia is considerably lower than in the times of SFRY and USSR. However, it will certainly increase in the future, leading to an intensification of cooperation with Krasnodar region which will not only be based on trade relations. [Projekat Ministarstva nauke Republike Srbije, br. 47007]